Ambulatory Movements, Team Dynamics and Interactions during Robot-Assisted Surgery - Ahmad, Nabeeha (BJU Int, 2016)
OBJECTIVE: To analyze ambulatory movements and team dynamics during robot-assisted surgery (RAS), and investigate whether congestion of the physical space associated with RA technology led to workflow challenges, or predisposed to errors and adverse events. METHODS: With IRB approval, we retrospectively reviewed 10 recorded RA radical prostatectomies in a single operating room (OR). OR was divided into 8 zones, and all movement were tracked and described in terms of start and end zones, duration, personnel, and purpose. Movement were further classified into avoidable (can be eliminated/improved) and unavoidable (necessary for completion of the procedure). RESULTS: Mean operative time was 166 minutes, of which ambulation constituted 27 minutes (16%). A total of 2,896 ambulatory movements were identified (mean=290 ambulatory movements/procedure). Most of movements were procedure-related (31%), and were performed by the circulating nurse. We identified 11 main pathways in the OR (Figure 1); the heaviest traffic was between the Circulating Nurse Zone, Transit Zone and Supply-1 Zone. Fifty percent of ambulatory movements were found to be avoidable. CONCLUSION: More than half of the movements during RAS can be eliminated with an improved OR setting. More studies are needed to design an evidence-based OR layout that enhances access, workflow and patient safety.